KESANTUNAN BERBAHASA DALAM PERSPEKTIF SOSIOLINGUISTIK - Hanafi, Muhammad (JURNAL ILMU BUDAYA, 2014)
Speech community concept can be seen/shown through three approaches; Firstly, on the basis oftheir common language forms, secondly by rules that regulate those common language forms,and thirdly from the perspective of the common cultural concepts. Speech community is possiblycreated if certain group of individuals, for the reason of common territory, professions, hobbieshave exactly the same language and possess the common judgement on any linguistic norms. Thesame case can also be projected to any speech communities in certain social, household,governmental, or religious domains to mention a few possibilitites.Keywords: linguis politnes, sociolinguistic, speech commuity.